Nutrients removal and substrate enzyme activities in vertical subsurface flow constructed wetlands for mariculture wastewater treatment: Effects of ammonia nitrogen loading rates and salinity levels. (June 2018) - Li, Meng; Liang, Zhenlin; Callier, Myriam D.; Roque d'orbcastel, Emmanuelle; Sun, Guoxiang; Ma, Xiaona; Li, Xian; Wang, Shunkui; Liu, Ying; Song, Xiefa
Abstract: This study aims to investigate the effects of ammonia nitrogen loading rates and salinity levels on nutrients removal rates and substrate enzyme activities of constructed wetland (CW) microcosms planted with Salicornia bigelovii treating mariculture wastewater. Activities of urease (UA), dehydrogenase (DA), protease (PrA) and phosphatase (PA) were considered. Using principal component analysis (PCA), nutrient removal index (NRI) and enzyme activity index (EAI) were developed to evaluate the effects. The results revealed that increasing ammonia nitrogen loading rates had positive effects on nitrogen removal rates (i.e. NH4 -N and DIN) and enhanced substrate enzyme activities. Compared with low salinity (i.e. 15 and 22), high salinity levels (i.e. 29 and 36) enhanced nutrients removal rates, DA and UA, but weaken PA and PrA. In conclusion, CW microcosms with Salicornia bigelovii can be used for the removal of nutrients under a range of ammonia nitrogen loadings and high salinity levels. Highlights: Both nutrients removal and substrate enzyme activities of marine CWs were evaluated. High ammonia nitrogen loading gave high N removal rates and enzyme activities. High salinities, i.e. 29 and 36, enhanced nutrients removal rates and activities of dehydrogenase and urease.